A silver triflate-catalyzed cascade of in situ-oxidation and allylation of arylbenzylamines. Issue 31 (3rd August 2016) - Wang, Junjiao; Yang, Shangdong
Graphical abstract: Highlights: A cascade of in situ-oxidation and allylation of arylbenzylamines. Mild oxidant, non-toxic allylation reagent, and highly compatible system. Various homoallylic amines are obtained up to 99% yields. The products can be transformed into various useful building blocks. Abstract: A silver-triflate catalyzed cascade of in situ-oxidation and allylation of arylbenzylamines is reported. The 2, 2, 6, 6-tetramethylpiperidine-1-oxoammonium tetrafluoroborate is employed as a mild oxidant which is compatible with both catalyst and ligand. Racemic BINAP is also utilized to assist with the catalyst in regulating the yields of products. Various homoallylic amines are obtained in 39–99% yields.